Combination of surfactant enhanced soil washing and electro-Fenton process for the treatment of soils contaminated by petroleum hydrocarbons. (15th April 2015) - Huguenot, David; Mousset, Emmanuel; van Hullebusch, Eric D.; Oturan, Mehmet A.
Abstract: In order to improve the efficiency of soil washing treatment of hydrocarbon contaminated soils, an innovative combination of this soil treatment technique with an electrochemical advanced oxidation process (i.e. electro-Fenton (EF)) has been proposed. An ex situ soil column washing experiment was performed on a genuinely diesel-contaminated soil. The washing solution was enriched with surfactant Tween ® 80 at different concentrations, higher than the critical micellar concentration (CMC). The impact of soil washing was evaluated on the hydrocarbons concentration in the leachates collected at the bottom of the soil columns. These eluates were then studied for their degradation potential by EF treatment. Results showed that a concentration of 5% of Tween ® 80 was required to enhance hydrocarbons extraction from the soil. Even with this Tween ® 80 concentration, the efficiency of the treatment remained very low (only 1% after 24 h of washing). Electrochemical treatments performed thereafter with EF on the collected eluates revealed that the quasi-complete mineralization (>99.5%) of the hydrocarbons was achieved within 32 h according to a linear kinetic trend. Toxicity was higher than in the initial solution and reached 95% of inhibition of Vibrio fischeri bacteria measured by Microtox ® method, demonstrating the presence of remaining toxic compounds even after the complete degradation. Finally, the biodegradability (BOD5 /COD ratio) reached a maximum of 20% after 20 h of EF treatment, which is not enough to implement a combined treatment with a biological treatment process. Highlights: Hydrocarbons extraction was enhanced with an increase of Tween ® 80 concentration. Heavy hydrocarbon fractions were better extracted with high Tween ® 80 concentration. Electro-Fenton is suitable for the improvement of hydrocarbon degradation in solution. Post electro-Fenton great biodegradability revealed further potential biodegradation.